2014
DOI: 10.3390/jcdd1030237
|View full text |Cite
|
Sign up to set email alerts
|

Cross Talk between NOTCH Signaling and Biomechanics in Human Aortic Valve Disease Pathogenesis

Abstract: Aortic valve disease is a burgeoning public health problem associated with significant mortality. Loss of function mutations in NOTCH1 cause bicuspid aortic valve (BAV) and calcific aortic valve disease. Because calcific nodules manifest on the fibrosa side of the cusp in low fluidic oscillatory shear stress (OSS), elucidating pathogenesis requires approaches that consider both molecular and mechanical factors. Therefore, we examined the relationship between NOTCH loss of function (LOF) and biomechanical indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 92 publications
0
7
0
Order By: Relevance
“…The effect of Notch1 inhibition is modulated by mechanical stress, and aortic VICs isolated from Notch1 +/– genotype mice and exposed to mechanical strain exhibit exaggerated αSMA expression, myofibroblastic differentiation and dystrophic calcific nodule formation compared to wild-type VICs ( 163 ). Similarly, exposure of human aortic VICs to oscillatory shear stress (OSS) in combination with a Notch1 inhibitor resulted in increased αSMA expression, where Notch1 inhibition alone resulted in calcific nodule formation with reduced αSMA expression ( 164 ). Genetic variations in NOTCH1 may predispose some individuals to aortic valvular inflammation in response to normal oscillatory shear stress ( 73 ).…”
Section: Mechanotransduction Pathways As Possible Therapeutic Targets...mentioning
confidence: 99%
“…The effect of Notch1 inhibition is modulated by mechanical stress, and aortic VICs isolated from Notch1 +/– genotype mice and exposed to mechanical strain exhibit exaggerated αSMA expression, myofibroblastic differentiation and dystrophic calcific nodule formation compared to wild-type VICs ( 163 ). Similarly, exposure of human aortic VICs to oscillatory shear stress (OSS) in combination with a Notch1 inhibitor resulted in increased αSMA expression, where Notch1 inhibition alone resulted in calcific nodule formation with reduced αSMA expression ( 164 ). Genetic variations in NOTCH1 may predispose some individuals to aortic valvular inflammation in response to normal oscillatory shear stress ( 73 ).…”
Section: Mechanotransduction Pathways As Possible Therapeutic Targets...mentioning
confidence: 99%
“…During embryonic development, the aortic root and the aortic valve originate from the second heart field cells. The NOTCH1 gene has been shown to be substantially involved in TAV development [30]. Mutations in the NOTCH1 gene are associated with the presence of BAV and the occurrence of aortic wall deformations [31].…”
Section: Cardiovascular Morbidity and Bicuspid Aortic Valve In Turner Syndromementioning
confidence: 99%
“…In zebrafish, the mechanosensitive channels Trpv4 and Trpp2 modulate endocardial calcium signaling and klf2a expression is necessary for valve morphogenesis and downstream pathway activation (Heckel et al, 2015; Steed et al, 2016b). Notch signaling is tightly involved in cellular mechanosensitive responses in human aortic valves (Godby et al, 2014) and Notch1 is a potent mechanosensor in adult arteries (Mack et al, 2017). More recently, it has been shown that stretch-sensitive channels from the Piezo family (Murthy et al, 2017) are important for vascular development (Li et al, 2014; Ranade et al, 2014) and lymphatic valve formation (Nonomura et al, 2018).…”
Section: Introductionmentioning
confidence: 99%